EDUKASI BUDIDAYA IKAN MELALUI FIELDTRIP SEKOLAH KRISTEN CARITAS AMBON DI MARINE SCIENCE STASION HILA - Loupatty, Joice W.; Fendjalang, Sophia N. M.; Jamal, Endang; Pattinasarany, Agapery Y.; Pattiasina, Bethsy J.; Borut, Ruku R. (Pattimura University, 2025)
This community service program aims to introduce aquaculture activities to students of Sekolah Kristen Caritas Ambon through a fieldtrip method at the Field Station of Marine Science in Hila. The activity is a collaboration between the Aquaculture Department of Pattimura University and the school, employing an interactive educational approach. The delivered materials included the introduction of cultured fish species, fish anatomy, types of culture systems (floating net cages and tidal ponds), as well as post-harvest facilities such as cold storage. This exploratory activity is designed to increase students' interest and understanding of aquatic ecosystems and the importance of environmental sustainability from an early age. Evaluation was conducted through interactive Q&A sessions. The results indicated high enthusiasm from students, teachers, and parents, as well as the achievement of the educational objectives. This activity supports the implementation of the Tri Dharma of Higher Education in the form of environmental and aquaculture-based educational outreach.